Total Service Long-Run Incremental Cost Modelling in Broadband FTTx Architectures - Ronald Romero Reyes; Thomas Bauschert (International Telecommunications Society (ITS), 2020)
This paper proposes an approach for the estimation of the cost contribution that FTTx broadband access networks make to the total service long-run incremental costs (LRIC) of the information services carried on these networks. The approach is applicable to the analysis of the techno-economic efficiencies of the business models enabled by the disaggregation/unbundling of the access network infrastructure. This is achieved by dimensioning first the access network for an expected service demand. The corresponding capital and operational expenditures are then calculated and apportioned to the services. The goal is to quantify the dependency of the LRIC on the architecture and the technologies used to deploy the access network. For selected business models, results are discussed for a case study that considers the provisioning of IPTV, VoIP and Internet services over FTTx networks implemented by active and passive optical networking technologies. The results show that the disaggregation of the access network may result in service cost savings compared to the traditional vertically integrated business model. Furthermore, different FTTx solutions based on active and passive technologies attain similar service costs.
Keywords: 330; Fixed broadband access networks; FTTx; Lon-Run Incremental Cost; Cost Allocation to Services